Increasing the slaughter weight of boars: Effects on performance and pork quality - S. Jaturasitha (2018)
Thirty-six crossbred boars were slaughtered with 90, 100, 110 and 120 kg live-weight. The measured carcass weights were 63, 70,81 and 89 kg, respectively. Slaughter weight had no significant effect on average daily gains and feed conversion efficiency although both measures tended to decline, particularly from 90 to 100 kg slaughter weight. Dressing percentage, lean percentage, backfat thickness and loin eye area significantly increased with slaughter weight. Effects of slaughter weight on meat pH, colour and water holding capacity were mostly insignificant. Shear force increased with weight until 110 kg were reached and sensory tenderness decreased. Skatole concentration in backfat increased with weight while flavour scoring and overall acceptance declined and an increasing number of panelists noted boar taint. In conclusion, it seems that the European Union threshold for boars of 80 kg carcass weight is still too high to completely exclude adverse effects on pork quality. © GSP, India.